STUDI KELAYAKAN POTENSI MINERAL TAMBANG PASIR-BATU MENGGUNAKAN PENDEKATAN LITOFASIES DAN PROSES GEOMORFIK PADA ALUR SUNGAI GENDOL PASCA ERUPSI GUNUNGAPI MERAPI 2010 - , Dhandhun Wacano; , Prof. Dr. rer. nat. Junun Sartohadi, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Merapi eruption in 2010 resulted in a material of 140 million cubic meters. About 35 million cubic meters eruption Materials is filling the Gendol River as far as 15 km. The materials experience the process of further eruptions in the form of depotition, mass movement, and sedimentation. Materials eruption such as sand and rock have economic potential for mining activities, especially as materials in concrete construction. The purpose of the study, namely: (1) to identify the distribution of the level of quality sand and stone mining based lithofacies characteristics and geomorphic processes (2) to calculate the volume of sediment of sand and stone mining, (3) to analyze the feasibility of mineral sand mining and stone potential based on the characteristic of material sediment. The method used is a field survey and laboratory analysis. Identification of lithofacies and geomorphological processes are carried out by a combination of visual interpretation of high-resolution satellite imagery and field surveys. Identification of the sediment quality distribution is conducted by analyzing in accordance with the requirements of coarse aggregate and fine aggregate in concrete construction. The volume of sediment is calculated by adding the measurement and reduction of sediment deposition in the channel. The feasibility of potential sediment is analyzed based on the quality and volume of sediment using a weighting AHP (analytical hierarchy process). The results showed that the flow of the river Gendol is scientifically not suitable for mining activities, although technically it can be done at certain locations. Mineable zone at the study site is at the center location (medial) for coarse aggregate (gravel), whereas for fine aggregate (sand) located at the downstream (early distal).